Svetlobna terapija za zdravljenje opeklinske rane - Tonin, Katarina (Rehabilitacija (Ljubljana), 2014)
The use of light therapy as additional therapy for healing of wounds is increasing. This case presents a 47-year old patient with deep dermal burns on the head, hands and trun. Open burn wounds on the head and in the front part of the elbow were treated with light therapy five times a week for 10 minutes. We used polarized, incoherent, lowlevel visible light (wave length 480 % 3400 nm, degree of polarization 95 %, power density 40 mW/cm2, light energy 2.4 J/cm2 at 10 cm distance of from the skin). The surface of wounds on the head was 25.1 cm2 before and 1.5 cm2 after 15 sessions of light therapy. The wound surface on the anterior part of the elbow was 18.5 cm2 before and 3.6 cm2 after 15 sessions of light therapy. The wound on head has healed in four weeks; the wound on elbow has healed in five weeks. Light therapy was continued for another week after healing for better epithelialisation. This case report showed that the healing of burn wound with light therapy could be successful.
Keywords: burn wounds; celjenje ran; fotobiostimulacija; fototerapija; opeklinske rane; photobiostimulation; Phototherapy; Wound Healing